Autonomic Nervous System Dysfunction In Hypertensive Patients: A Heart Rate Variability (HRV) Analysis - Majeed, Mutayyaba; Munir, Hina; Niazi, Zehra; Asad, Ayesha; Javed, Najam-ul-Sehar; Amin Hashmi, Mashhood Shahid (Journal of Neonatal Surgery, 2025)
Background: Hypertension, the most prevalent cardiovascular disorder, significantly escalates the risks of stroke, myocardial infarction, and renal diseases. It is believed that an imbalance of the autonomic nervous system (ANS), particularly heightened sympathetic tone and reduced parasympathetic regulation, underlies its pathogenesis. One of the non-invasive approaches to study the ANS is the analysis of heart rate variability (HRV). Objectives: To evaluate autonomic nervous system impairment in hypertensive patients and to evaluate the heart rate variability (HRV); then compare the findings with normal subjects (normotensive) to establish the statistical significance. Study design: Cross-sectional comparative study. Place and duration of study: July 2024 to December 2024, Independent University Hospital, Faisalabad. Methods: The study was carried out on 100 patients with hypertension, and 100 age matched normotensive controls. A 5-minute ECG and measurement of HRV were made during resting state. Parameters in time-domain and in frequency-domain were analyzed. Descriptive statistics were determined with mean and standard deviation and independent t-tests in order to determine the differences between groups. All comparisons were measured to be statistically important at p < 0.05. Results: One hundred hypertensive patients (mean age: 54.22 9.6 years) and one hundred normotensive controls (mean age: 53.72 8.9 years; p = 0.67) were studied. There are also lower HRV indexes; SDNN or Standard Deviation of Normal-to-Normal intervals, a key measure of HRV (36.4 12.3 ms vs. 48.7 14.1 ms, p < 0.001) and RMSSD or Root Mean Square of Successive Differences (21.1 9.2 ms vs. 31.5 10.7 ms, p < 0.001) in hypertensive subjects. Frequency-domain also indicated lower parasympathetic (HF) and greater sympathetic (LF/HF ratio) modulation comparisons of hypertensive compared to controls (p < 0.05). These results confirm the existence of autonomic alteration among hypertensive patients. Conclusion: A major dysfunction of the autonomic mechanisms related to a low heart rate variability is seen in hypertensive patients. The results show reduced activity of parasympathetic system and the increased sympathetic dominance. The HRV analysis is useful and non-invasive to determine autonomic balance in hypertensive people and can be to help in early detection and risk stratification. The regular use of HRV in the chain of hypertension treatment and management would increase patient-centered approaches.